2018
DOI: 10.1177/0098628318816155
|View full text |Cite
|
Sign up to set email alerts
|

Science, Story, and Structure: Framing the Conversation for Psychology Faculty and Librarian Information Literacy Collaboration

Abstract: This case study illuminates the effectiveness of collaboration between a librarian and psychology faculty as they use the Framework for Information Literacy for Higher Education and the Guidelines for the Undergraduate Psychology Major to improve an assignment and frame their conversation on scaffolding students’ information literacy skill development. Faculty and librarian collaboration is critical to supporting student learning. Disciplinary standards may be effective tools for librarians and faculty to fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…They concluded that students need to learn information and technology skills in order to become effective information users because there is a discrepancy between the skill set of information users and the amount of information that is available. These results were also supported by the study of Lai and Graber (2016) and Brady and Malik (2018), that intellectual property rights are also helpful for information exchange, utilisation, acquisition, and processing. Intellectual property laws essentially enable the copying and sharing of these digital items, which is frequently an unattributed copy of someone else's work that results in the misuse of that person's intellectual property.…”
Section: Discussionsupporting
confidence: 64%
“…They concluded that students need to learn information and technology skills in order to become effective information users because there is a discrepancy between the skill set of information users and the amount of information that is available. These results were also supported by the study of Lai and Graber (2016) and Brady and Malik (2018), that intellectual property rights are also helpful for information exchange, utilisation, acquisition, and processing. Intellectual property laws essentially enable the copying and sharing of these digital items, which is frequently an unattributed copy of someone else's work that results in the misuse of that person's intellectual property.…”
Section: Discussionsupporting
confidence: 64%
“…What does not vary is the low evaluation of the library as a preferred SL. This outcome may be due to the students' lack of understanding of libraries' operational complexities (Head, 2008) and to the fact that IL is no longer an exclusive domain of the library and information professionals (Brady and Malik, 2019 From an underlying perspective, factor structures do not differ by country. Therefore, hypothesis H5 holds.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the fact that faculty engagement/faculty collaboration was identified as a challenge in the delivery of information literacy, it is being recommended that faculty and librarian collaboration be considered as a critical component of the methodology used in supporting student learning. As postulated by Brady and Malik (2018), information literacy skills development can be heightened by librarians and faculty using a shared vocabulary to engage in meaningful conversation about the planning and implementation of course assignments [and] the critical examination of various paths to information literacy through the engagement of librarian and faculty.…”
Section: Recommendationsmentioning
confidence: 99%